2023
DOI: 10.1155/2023/9980011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electronic Cigarettes in Dental Caries: A Scoping Review

Sumit Gaur,
Rupali Agnihotri

Abstract: Dental caries, a predominant childhood and adolescence affliction, has numerous factors implicated in its pathogenesis. Electronic cigarettes (ECs) have recently gained popularity among the younger population. Various factors, such as the EC liquid composition and aerosols, are associated with the development of dental caries. This review explains numerous EC-related factors which may lead to dental caries. An electronic search was conducted in Medline (Pubmed), Scopus, and Embase databases to evaluate the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(150 reference statements)
0
1
0
Order By: Relevance
“…E-cigarettes and their oral health consequences are beginning to receive attention in research [5,18,19]. In a scoping review of e-cigarettes and dental caries, the reviewers suggested e-liquids and e-cigarette aerosols contributed to dental caries [20]. In another literature review, most of the studies did not have oral health effects as their primary outcome, and the researchers rated the quality of the evidence as weak [18].…”
Section: Introductionmentioning
confidence: 99%
“…E-cigarettes and their oral health consequences are beginning to receive attention in research [5,18,19]. In a scoping review of e-cigarettes and dental caries, the reviewers suggested e-liquids and e-cigarette aerosols contributed to dental caries [20]. In another literature review, most of the studies did not have oral health effects as their primary outcome, and the researchers rated the quality of the evidence as weak [18].…”
Section: Introductionmentioning
confidence: 99%